Indium thiospinel In1−x□xIn2S4 – structural characterization and thermoelectric properties. Issue 23 (21st May 2019) - Wyżga, Paweł; Veremchuk, Igor; Himcinschi, Cameliu; Burkhardt, Ulrich; Carrillo-Cabrera, Wilder; Bobnar, Matej; Hennig, Christoph; Leithe-Jasper, Andreas; Kortus, Jens; Gumeniuk, Roman
Abstract : Structural disorder induced by β↔α polymorphic transformation strongly affects electronic and thermal transport in indium thiospinel. Abstract : A detailed study of polycrystalline indium-based In1− x □ x In2 S4 ( x = 0.16, 0.22, 0.28, and 0.33) thiospinel is presented (□ – vacancy). Comprehensive investigation of synthesis conditions, phase composition and thermoelectric properties was performed by means of various diffraction, microscopic and spectroscopic methods. Single-phase α- and β-In1− x □ x In2 S4 were found in samples with 0.16 ≤ x ≤ 0.22 and x = 0.33 (In2 S3 ), respectively. In contrast, it is shown that In0.72 □0.28 In2 S4 contains both α- and β-polymorphic modifications. Consequently, the thermoelectric characterization of well-defined α- and β-In1− x □ x In2 S4 is conducted for the first time. α-In1− x □ x In2 S4 ( x = 0.16 and 0.22) revealed n-type semiconducting behavior, a large Seebeck coefficient (>|200| μV K −1 ) and moderate charge carrier mobility on the level of ∼20 cm 2 V −1 s −1 at room temperature (RT). Decreases in charge carrier concentration (increase of electrical resistivity) and thermal conductivity (even below 0.6 W m −1 K −1 at 760 K) for larger In-content are observed. Although β-In0.67 □0.33 In2 S4 (β-In2 S3 ) is a distinct polymorphic modification, it followed the abovementioned trend in thermal conductivity and displayed significantly higher charge carrier mobility (∼10 4 cm 2 V −1 s −1 at RT). These findings indicate that structural disorder in the α-modification affects both electronic and thermal properties in this thiospinel. The reduction of thermal conductivity counterbalances a lowered power factor and, thus, the thermoelectric figure of merit ZT max = 0.2 at 760 K is nearly the same for both α- and β-In1− x □ x In2 S4 .